Pseudoeosinophilia with Abnormal WBC Scattergram: an Important Diagnostic Clue on Hematology Analyzer - Prabhu, Swathi C; Tahlan, Anita; Sharma, Shreya; Lehl, Sarabmeet S (Nepalese Medical Journal, 2021)
Malaria is one of the most common parasitic diseases causing a significant burden on health care, especially in India. Light microscopy, the gold standard for malaria diagnosis is time-consuming especially in a setup where the caseload is high and parasite index is low. Knowledge of abnormal scattergrams by the malarial parasite is very essential to suspect malaria and screen those cases thoroughly on a peripheral smear for accurate diagnosis. A timely and accurate diagnosis is crucial to the prognosis of this disease. Herein, we report a case of a 40-year-old male from Punjab who presented to the emergency with fever and an altered sensorium. Analyzer showed characteristic pseudo eosinophilia with greying of neutrophil eosinophil zone with double eosinophil cluster. According to flagging rules because of eosinophilia, peripheral blood film (PBF) was made and examined, which revealed Plasmodium falciparum gametocytes.